Kinetic study of fenton oxidation for real rubber wastewater - Lim, Hui Jhen (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Rubber wastewater usually contains pollutants such as dust, oil, grease, organic metal, heavy metal, and other chemicals. If the effluent is not properly managed, it can pollute the water supply or surrounding water bodies. Various parameters, including pH (3-13), catalyst concentration (20-80 mg L-1) and oxidant concentration (0.03-0.3 mL L-1), were used to study the effects on Fenton oxidation. The results appeared that the Fenton oxidation process took place well in acidic condition with optimum pH 3. The Fenton oxidation process rate increased when the catalyst concentration increases. The Fenton oxidation process is favour with increase in catalyst concentration and oxidant concentration. However the percentage removal of COD value decreased once the amount of oxidant concentration reaches more than 0.05 mL L-1. The kinetic study data fitted better in pseudo-second order kinetic model. The Fenton oxidation process followed the pseudo-second order kinetic model showing that catalyst concentration and oxidant concentration are a rate-determining step during Fenton oxidation process. The initial COD value of rubber wastewater is 1053mg/L. Under optimal conditions of Fe2+ = 80 mg/L, H2O2 = 0.05 mL/L and reaction time = 120 min, a maximal COD removal (73.31 %) has been achieved. It can be concluded that Fenton oxidation is effective for the treatment of rubber wastewater..